Evaluation of the Implementation of IFRS S1 and IFRS S2 in Banking Sector Sustainability Reporting for the 2023 Period - Harahap, Hanna Meyrani; Danut, Yohana; Aritonang, Ramona; Yulita, Wita; daniel, Daniel; Ramadhan, Yanuar (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The Paris Agreement in 2015 is an international agreement to reduce the rise in global temperature and reduce its impact. As a developing country with the effects of greenhouse emissions that have a significant impact, Indonesia participates in reducing greenhouse gas emissions with a net zero emission target by 2060. This study aims to analyze the disclosure by banks based on the minimum requirements set out in the International Financial Reporting Standards Sustainability (IFRS S). The method used is a qualitative descriptive of the aspects of governance, strategy, risk management as well as the matrix and targets disclosed in the 2023 sustainability report of seven banks that are committed to the OJK to achieve Indonesia's net zero emission target. The result of this study is that in the aspect of governance, all banks have a unit that is responsible for implementing and supervising sustainability aspects related to governance, environmental and social. However, there are still banks that are inadequate in disclosing aspects of strategy, risk management, as well as matrices and targets.